Protesta e indignación global. - Bringel, Breno (CLACSO, 2017)
The book "Global Protest and Indignation" is a work co-published by FAPERJ (Fundação de Amparo à Pesquisa do Estado do Rio de Janeiro) and summarizes the organizational and analytical effort carried out by Breno Bringel and Geoffrey Pleyers on the openMovements platform. This platform is part of the independent editorial initiative openDemocracy.The book focuses on the study of social movements and popular organizations that fight for citizen rights, social justice, common goods and radical democracy. Its main objective is to offer a significant contribution to the debate on the present and the future of these movements, becoming an indispensable reference in this field.The work uses the critical social sciences as a tool for political intervention and militant commitment in the search for equality and human emancipation. Through analysis and reflection, the authors examine protest and outrage on a global level, exploring its importance, its impact, and its implications for contemporary society.In short, "Global Protest and Outrage" is a book that seeks to analyze and understand social movements and popular organizations that fight for important social and political causes. Its critical approach and its commitment to equality and human emancipation make it a relevant work for the study of these issues.